Five new species of Hemibrycon (Characiformes: Characidae) from the Río Magdalena basin, Colombia - César Román-Valencia (Revista de Biología Tropical, 2010)
Five new fish species of the genus Hemibrycon are described from the Río Magdalena basin, Colombia, using morphometric, meristic and osteological characters. Hemibrycon paez (n=40) differs in number of lateral line scales (39 to 42 vs. 43 to 54), by the number of scales between lateral line and anal-fin origin (6 to 7 vs. 4 to 5) and between lateral line and dorsal-fin origin (6 to 7 vs. 8); H. quindos (n=66) distinguished from its congeners by one autopomorphy: Males with cartilaginous protuberance, rounded on the anal fin ray branched, along all rays (vs. cartilaginous protuberance not present on anal-fin rays in males), by the maxilla without a fold on its anterior end (vs. maxilla with folding only at posterior end), by the number of pored scales in the lateral line (35 to 40 vs. 40 to 46); H. raqueliae (n=117) distinguished by a widened first tooth on the maxilla with the remaining teeth decreasing sharply in size (vs. first tooth of maxilla slender, remaining teeth gradually diminishing), by the first maxilla tooth pentacuspid and wider than the others (vs. first tooth on maxilla unicuspid or tricuspid and of same size as the others); H. virolinica (n=34) distinguished by the posterior end of the extrascapular spine surpassing the postemporal (vs. posterior end of extrascapular not exceeding postemporal spine), by having the posterior end of the first proximal pteryigiophores of dorsal fin of the same size as the anterior edge (vs. the posterior end of the first proximal pteryigiophores of dorsal fin more elongated than the anterior edge); and H. yacopiae (n=78) is distinguished by the following autopomorphic characters: first laterosensorial infraorbitals canal in contact with the posterior end of antorbital (vs. laterosensorial canal not reaching posterior end of antorbital), by the tip of the supraoccipital spine widened (vs. supraoccipital spine acute), by the posterior end of ectopterygoids failing to come in contact with the quadrate bone (vs. in contact); by the posterior edge of palatine more widened than the anterior edge of ectopterygoids (vs. posterior edge of the palatine approximately the same size, except for H. paez). Rev. Biol. Trop. 58 (1): 339-356. Epub 2010 March 01. Cinco nuevas especies son descritas para la cuenca del Río Magdalena, Colombia, con base en caracteres morfométricos, merísticos y osteológicos. Hemibrycon paez se distingue por el número de escamas en la línea lateral (39 a 42 vs. 43 a 54), entre la línea lateral y el origen de la aleta anal (6 a 7 vs. 4 a 5), y entre la línea lateral y el origen de la aleta dorsal (6 a 7 vs. 8). H. quindos se distingue por una autopomorfia: machos con protuberancias cartilaginosas redondeadas sobre los radios ramificados de la aleta anal, sobre toda su extensión (vs. no presentes en los radios de las aletas anal en machos), la maxila que no posee un plegamiento en su extremo posterior (vs. maxilar con doblamiento en su extremo posterior), por el número de escamas con poros en la línea lateral (35 a 40 vs. 40 a 46). H. raqueliae, se distingue por presentar el primer diente del maxilar ensanchado al comparar con los demás dientes que disminuye abruptamente en tamaño (vs. Primer diente del maxilar delgado, los demás dientes disminuyen gradualmente), por presentar el primer diente de la maxila pentacúspide y más ancho que los demás (vs. primer diente sobre la maxila uni o tricúspide y de igual tamaño que los otros. H. virolinica se distingue por poseer en el extremo posterior del extraescapular una espina que sobre pasa el postemporal (vs. extremo posterior del extrascapular no sobre pasa la espina del postemporal), por tener el extremo posterior del primer pterigióforo proximal de la aleta dorsal del mismo tamaño que el borde anterior (vs. el extremo posterior del primer pterigióforo proximal de la aleta dorsal mas alargado que el borde anterior). H. yacopiae se diferencia por una autopomorfia: el canal laterosensorial sobre primer infraorbital en contacto con el extremo posterior del antorbital (vs. el canal laterosensorial no alcanza el extremo posterior del antorbital), por el extremo de la espina supraoccipital ancha (vs. espina supraoccipital aguda), por el extremo posterior del ectopterigoide no en contacto con el cuadrado (vs. en contacto), por el borde posterior del palatino más ancho que el borde anterior del ectopterigoide (vs. borde posterior del palatino aproximadamente del mismo tamaño).